Step Counting and Energy Expenditure Estimation in Patients With Chronic Obstructive Pulmonary Disease and Healthy Elderly: Accuracy of 2 Motion Sensors - Furlanetto, Karina C.; Bisca, Gianna W.; Oldemberg, Nicoli; Sant'Anna, Thais J.; Morakami, Fernanda K.; Camillo, Carlos A.; Cavalheri, Vinicius [UNESP]; Hernandes, Nidia A. [UNESP]; Probst, Vanessa S.; Ramos, Ercy M. [UNESP]; Brunetto, Antonio F.; Pitta, Fabio [UNESP] (W B Saunders Co-elsevier Inc, 2010)
Furlanetto KC, Bisca GW, Oldemberg N. Sant'Anna TJ, Morakami FK, Camillo CA, Cavalheri V, Hernandes NA, Probst VS, Ramos EM, Brunetto AF, Pitta F. Step counting and energy expenditure estimation in patients with chronic obstructive pulmonary disease and healthy elderly: accuracy of 2 motion sensors. Arch Phys Med Rehabil 2010;91:261-7.Objective: To compare the accuracy of 2 motion sensors (a pedometer and a multisensor) in terms of step counting and estimation of energy expenditure (EE) in patients with chronic obstructive pulmonary disease (COPD) and in healthy elderly.Design: In this descriptive study, all participants wore both motion sensors while performing a treadmill walking protocol at 3 different speeds corresponding to 30%, 60%, and 100% of the average speed achieved during a six-minute walk test. As criterion methods, EE was estimated by indirect calorimetry, and steps were registered by videotape.Setting: Research laboratory at a university hospital.Participants: Patients with COPD (n=30; 17 men; mean age +/- SD, 67 +/- 8y; mean forced expiratory volume in the first second [FEV(1)] predicted +/- SD, 46% +/- 17%; mean body mass index [BMI] +/- SD, 24 +/- 4kg.m(2)) and matched healthy elderly (n=30; 15 men; mean age +/- SD, 68 +/- 7y; mean FEV(1) predicted +/- SD, 104% +/- 21%; mean BMI +/- SD, 25 +/- 3kg.m(2)).Interventions: Not applicable.Main Outcome Measure: Step counting and EE estimation during a treadmill walking protocol.Results: The pedometer was accurate for step counting and EE estimation in both patients with COPD and healthy elderly at the higher speed. However, it showed significant underestimation at the 2 slower speeds in both groups. The multisensor did not detect steps accurately at any speed, although it accurately estimated EE at all speeds in healthy elderly and at the intermediate and higher speeds in patients with COPD.Conclusions: In both patients with COPD and healthy elderly, the multisensor showed better EE estimates during most walking speeds than the pedometer. Conversely, for step counting, accuracy is observed only with the pedometer during the higher walking speed in both groups.
Keywords: Pulmonary disease; chronic obstructive; Rehabilitation